Pemanfaatan Model Pembelajaran Problem Based Learning Terhadap Peningkatan Hasil Belajar Peserta Didik Pada Pembelajaran Kimia - Aliffah, Shyiba Yunia (LPPM Institut Pendidikan Nusantara Global, 2024)
This review activity aims to show the effectiveness of applying the problem based learning model to learning outcomes by reviewing several other research journals related to the variables being reviewed. The review focused on articles with a sample of high school students studying chemistry. Data collection was carried out on the Google Scholar, Mendeley and Scimago databases through a review of 26 national journals. The review method is carried out by summarizing, namely the technique of conducting a review by rewriting the source, either from a journal or book, in your own words, taking into account research trends in PBL learning models on learning outcomes from each source and assisted by the VOSviewer application, namely a visualization and network analysis application used to describe relationships between bibliometric data elements, such as authors, keywords, or research subjects. The results of the review taken from data from 7 high school level schools throughout Indonesia showed that the average pre-test score was 39.67%, while the average post-test score obtained was 86.05%. The average N-gain value obtained was 0.75>0.70, which shows that the PBL learning model can improve learning outcomes in chemistry learning material in the high category